Lifetime of the HCEI spark gap switch for linear transformer drivers; Pulsed Power Conference (PPC) - Kim A. A. Aleksandr Andreevich; Mazarakis M. G. Mikhail Gerasimovich; Sinebryukhov V. A. Vadim Anatoljevich; Volkov S. N. Sergey Nikolaevich; Alekseenko V. M. Vitaly Mikhaylovich; Kondratjev S. S. Sergey Sergeevich; Vasiljev S. V. Sergey Valerievich (2015, 2015)
Title screen